Turning Trash into Treasure: The Current Landscape and Future of Waste-to-Energy Initiatives in India - Sati, Kirtika; Vats, Aditi (International Journal of Environment, Agriculture and Biotechnology, 2024)
Waste management in India has long been a pressing challenge, exacerbated by rapid urbanization and population growth. Among the various strategies to tackle this issue, waste-to-energy (WtE) initiatives have emerged as a promising solution, converting municipal solid waste into usable energy. This paper explores the current landscape of WtE initiatives in India, assessing their effectiveness, challenges, and future prospects. Despite the potential of WtE technologies to mitigate waste disposal problems and contribute to renewable energy production, their implementation in India faces significant hurdles, including technological, financial, and regulatory barriers. The existing WtE projects across different states, highlighting successful case studies such as the Okhla WtE plant in Delhi and the Narela-Bawana plant, which have demonstrated considerable capacity in waste processing and energy generation. Furthermore, we have analysed the policy framework supporting WtE projects, including government incentives and regulations under the Swachh Bharat Mission and the National Policy on Biofuels. The review also addresses the socio-environmental impact of WtE plants, considering public perception, environmental concerns, and the role of informal waste sectors. Challenges such as high capital costs, operational inefficiencies, and the need for improved waste segregation at the source are discussed, alongside potential solutions and technological advancements that could enhance WtE viability. Finally, we have outlined a roadmap for the future of WtE in India, advocating for integrated waste management systems, stronger regulatory frameworks, and increased public-private partnerships to foster sustainable development. This paper aims to provide a comprehensive overview of India's WtE landscape, offering insights and recommendations for stakeholders and policymakers to optimize waste management and energy production.